A Theoretical Study for Excitation of Electrons Collides with Positive Nitrogen Ions - S. Kadhim, Hawraa; A. Khalaf , Alaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Nitrogen ions, principally singly ionized nitrogen (N II) and doubly ionized nitrogen (N III), significantly affect different atomic, molecular, and astrophysical studies fields. as a result of their frequent occurrence in stellar atmospheres, interstellar media, and planetary nebulae, analysis of their spectral lines provides valuable details on environmental conditions such as temperature, density, and ionization states. This study indicated that N II and N III are excited by electron collisions for transition states. The Born-Bethe approximation was used to calculate the integral and differential cross-sections as well as the generalized oscillation strength. The results were agreed with other references in various transitions.